2020
DOI: 10.1177/1934578x20922382
|View full text |Cite
|
Sign up to set email alerts
|

A New Polyoxygenated Cyclohexene From the Rhizomes of Globba pendula Roxb.

Abstract: A new polyoxygenated cyclohexene, globbanol A (1), 2 other cyclohexene derivatives, crotepoxide (2) and boesenboxide (3), along with a chalcone, 2ʹ- hydroxy-4,4ʹ,6ʹ-trimethoxy-chalcone (4) were isolated from the rhizomes of Globba pendula Roxb. ( Zingiberaceae) of Vietnam. Their structures were elucidated on the basis of extensive analysis of high-resolution electrospray ionization mass spectrometry and NMR spectral data. Absolute configuration of new compound was determined by circular dichroism spectra. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Crotepoxide was first isolated in 1968 from Croton macrotachyus and thereafter after that, for the last ten years, has been isolated from several medicinal plant like Croton alienus (Rotich et al 2022), Globba pendula (Ngo et al 2020), Kaempferia angustifolia (Tang et al 2014Yeap et al 2017) and Kaempferia rotunda (Diastuti et al 2020). This compound was first isolated from Kaempferia rotunda by Pancharoen (Pancharoen et al 1996) reported that crotepoxide from K. rotunda represented negative values in an antifeedant assay.…”
Section: In Vitro Antioxidant Assay Of Isolated Compoundmentioning
confidence: 99%
“…Crotepoxide was first isolated in 1968 from Croton macrotachyus and thereafter after that, for the last ten years, has been isolated from several medicinal plant like Croton alienus (Rotich et al 2022), Globba pendula (Ngo et al 2020), Kaempferia angustifolia (Tang et al 2014Yeap et al 2017) and Kaempferia rotunda (Diastuti et al 2020). This compound was first isolated from Kaempferia rotunda by Pancharoen (Pancharoen et al 1996) reported that crotepoxide from K. rotunda represented negative values in an antifeedant assay.…”
Section: In Vitro Antioxidant Assay Of Isolated Compoundmentioning
confidence: 99%
“…4 We previously reported the isolation of one new polyoxygenated cyclohexene, globbanol A (1), along with two other cyclohexene derivatives, crotepoxide (2) and boesenboxide (3), and a chalcone, 2 ′ -4,4 ′ ,6 ′ -trimethoxychalcone (4), from the ethyl acetate extract of the rhizomes of G. pendula. 5 In this study, various extracts of G. pendula rhizomes were screened for in vitro anti-inflammatory activity on lipopolysaccharide-stimulated RAW 264.7 macrophages. The extract possessing the best activity was then further investigated for in vivo anti-inflammatory activity in an experimental mouse model with collagen antibody-induced arthritis (CAIA), as well as for acute toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…rhizomes by using column chromatography. 24 Various terpenoids were reported to be the major constituents of G. reflexa Craib rhizomes. 25 New compounds from G. pendula Globba schomburgkii Hook.f.…”
Section: Antibacterial Drugsmentioning
confidence: 99%